5-HT3 receptor antagonists do not alter spontaneous contraction of pregnant myometrium in vitro. Issue 1 (February 2015) - Lin, Xuemei; Du, Yu; Tang, Yuying; Zeng, Kui; Ni, Juan; Liu, Jin; Zhou, Jie
<x xml:space="preserve">Abstract</x> Highlights 5-HT3 receptor antagonists are used widely in pregnancy. The effects of 5-HT3 receptor antagonists on uterine contractility are unknown. Ondansetron, granisetron and tropisetron have no effect on myometrial contractility in vitro.